2017
DOI: 10.12691/jfa-5-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Inventory Management and SMEs Profitability. A Study of Furniture Manufacturing, Wholesale and Eatery Industry in Delta State, Nigeria

Abstract: Inventory constitutes bulk of current assets small and medium scale enterprises (SMEs) such as bakeries, fast food/eateries, chain stores and furniture making firms. SMEs need to understand the true costs associated with inventory management and poor inventory productivity so as to be able to review the benefits of alternative approaches. The objective of the study was to examine the effect of inventory management on profitability of SMEs in Nigeria. The study used a descriptive research design. The population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
1
7
1
Order By: Relevance
“…The study recommended that practices such as JIT be adopted for effective inventory management. Results were also similar for Otuya and Eginiwin (2017) in Nigeria and Nirujah (2015) in Sri Lanka.…”
Section: Literature Reviewsupporting
confidence: 57%
See 1 more Smart Citation
“…The study recommended that practices such as JIT be adopted for effective inventory management. Results were also similar for Otuya and Eginiwin (2017) in Nigeria and Nirujah (2015) in Sri Lanka.…”
Section: Literature Reviewsupporting
confidence: 57%
“…Inventory ties up substantial amount of a firm's capital and the efficient management of the inventory would ensure the survival and sustainability of the firm Several empirical studies have been embarked upon on inventory management on aspects of financial performance but no research has been done on inventory management and financial sustainability. A lot of researchers looked at inventory management and its effect on financial performance (Karadag, 2018;Amahalu et al, 2018;Wanjira and Njagiru, 2018;Bawa et al, 2018;Mulindabigwi and Mulyungi, 2017), likewise inventory management and its effect on profitability (Otuya and Eginiwin, 2017;Nirujah, 2015). To the best of our knowledge, there hasn't been any research on inventory management and its effect on financial sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Credit policy's impacts are either acceptable to create development and earnings or negative enough to resist bending losses. This resemblance is due to each manager's goal of efficiently and successfully collecting contributions while boosting cash flow (Otuya & Eginiwin, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The study showed clearly that SME owners need a business strategy to improve and enhance corporate efficiency that can contribute to business continuity. Effective strategies must meet both government and environmental wide business objectives [13]. Business strategy suitable for small-to medium-sized company managers / owner-managers [14].…”
Section: 11mentioning
confidence: 99%